L’HARMONISATION DE LA FISCALITÉ ENVIRONNEMENTALE DANS L’UNION EUROPÉENE : UNE ÉTUDE COMPARATIVE - Toma Elena (Annals of the University of Oradea: Economic Science, 2009)
Environmental protection issues took magnitude in recent years, being included on the list of priorities of the European Union. To reduce the negative externalities, a solution of compromise is taxing products whose consumption or production creates pollu